Healthy African American Families in the 21st Century: Navigating Opportunities and Transcending Adversities. Issue 3 (23rd May 2019) - Murry, Velma McBride
Abstract : Objective: To identify pathways through which African American families successfully negotiate and navigate stressful life events to facilitate positive family functioning, relationships, and healthy developmental outcomes in their children. Background: Despite the advancement of African Americans since passing of the 1965 Civil Rights Act, racism remains a major stressor that affects everyday life experiences of 21st‐century African American families. Little is known about the cascading effects of race‐related exposure on processes in African American families, nor about what promotes healthy functioning among African American families. Method: Three waves of data on 867 families participating in the Family and Community Health Study were analyzed to identify pathways that forecast family functioning and developmental outcomes of youth as they transitioned from middle childhood to late adolescence. Results: Stressful life events heightened maternal depression and anxiety, which were associated with a more cynical and hostile worldview and poorer quality of family relations. Parenting practices and family relationship quality were linked with children's self‐pride, which was closely associated with more optimistic worldview. Self‐pride was also associated with future aspirations among youth, and future‐oriented youth tended to engage in fewer self‐harm behaviors as they transitioned from middle childhood to early adolescence. Conclusion: Reframing one's life situation, despite exposure to racial discrimination, serves a protective function for African American families. Exerting a sense of agency, internal will, capacity, and strength are effective strategies to transcend adversities. Implications: That positive worldview can render more manageable family outcomes for African Americans, regardless of socioeconomic status, is worth considering in research, clinical practice, and preventive interventions.